The experience of dynamic media : works from the Dynamic Media Institute at Massachusetts College of Art and Design : 2006-2010 - Kubasiewicz, Jan; Quackenbush, Joe; Lucid, Brian; Kaza, Gunta; Karatzas, Evan; Bottorf, Toby; Smith, Ronald Bruce; Owens, Colin; Shaw, Heather; Ludvino, Dennis; Susi, Lou (Dynamic Media Institute, Massachusetts College of Art and Design, 2010)
"The Experience of Dynamic Media, the second book publication of the Dynamic Media Institute, the graduate program in communication design at Massachusetts College of Art and Design in Boston, was published on the occasion of its tenth anniversary. Combined with the previous publication titled The Language of Dynamic Media published in 2005, the books cover work from the Dynamic Media Institute between 2000 and 2010. This edition is organized in several sections. “Faculty Perspectives” includes short essays by DMI professors and visiting faculty, each sharing their individual philosophy and various approaches to dynamic media design education. “Featured Projects” presents student work through articles excerpted from the larger thesis dissertations. “Collaborations” presents examples of extracurricular projects which were developed between DMI and outside partners, as well as a series of DMI student-curated exhibitions. “Thesis Abstracts” presents all MFA degree thesis abstracts from 2006 to 2010."--Resumé vydavatele
Keywords: Massachusetts College of Art; 2006-2010; 2001-2010; vysoké umělecké školy -- Spojené státy americké -- 2001-2010; studium a výuka -- Spojené státy americké -- 2001-2010; mediální umění; art academies -- United States -- 2001-2010; study and teaching -- United States -- 2001-2010; media arts; jubilejní publikace; jubilee books